Research and development in the Muslim society - Babu Sahib, Hikmatullah (IIUM Press, 2005)
Despite clear-cut exhortation from the Qur’ān and Sunnah, Muslims are not showing much interest in R&D. Many Muslims are finding comfort in simply importing foreign goods and solutions to enrich their lives. Data analyses show that the Muslim world is far behind other countries in terms of research and development. There exists some misunderstanding in the Muslim mind on the meaning and role of research and development. There is a need for sustained research in all aspects of the society for it to develop as envisaged by Islam.